2013
DOI: 10.3390/molecules18021660
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polygalacturonases by Aspergillus section Nigri Strains in a Fixed Bed Reactor

Abstract: Polygalacturonases (PG) are pectinolytic enzymes that have technological, functional and biological applications in food processing, fruit ripening and plant-fungus interactions, respectively. In the present, a microtitre plate methodology was used for rapid screening of 61 isolates of fungi from Aspergillus section Nigri to assess production of endo- and exo-PG. Studies of scale-up were carried out in a fixed bed reactor operated under different parameters using the best producer strain immobilised in orange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Screening is often the first step to select microorganisms with characteristics intended for Industrial applications, which allows the characterization and selection of fungal strains with optimal enzyme production (Maciel et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Screening is often the first step to select microorganisms with characteristics intended for Industrial applications, which allows the characterization and selection of fungal strains with optimal enzyme production (Maciel et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This allows for the characterization and selection of fungal strains with optimum enzyme production. In addition, the information obtained adds value to these microbial resources preserved in culture collections (Maciel et al, 2013).…”
Section: Screening For Pectinase Productionmentioning
confidence: 99%
“…Moreover, Maller et al (2011) concluded that agro-industrial residues, such as orange and lemon peels, induced production of high levels of PG by A. niveus. The use of orange peels can be highly economical at the industrial scale for PG production (Maciel et al, 2013). A. niger URM 4645, when cultured using yellow passion fruit peels without the addition of nutrient solution, produced endo-PG, exo-PG, PL, and PE.…”
Section: Production Of Pectinolytic Enzymesmentioning
confidence: 99%
See 2 more Smart Citations